Demand-side management via photovoltaic generation with storage in the context of the brazilian tariff model - Rodrigues, Lucas Furtado; Carmo, Bruna Karla Soares do; Gomes, Andresa Aparecida Lemes; Queiroz, Anderson Rodrigo de; Lima, José Wanderley Marangon; Ribeiro, Paulo Fernando (Revista Hipótese, 2018)
With the advance of electric power generation produced along with the load consumption, allied with the current energy charging scenario in Brazil, this work presents demand-side management (DSM) in a microgrid. Comparative studies are carried out between three different models applied in the context of the white and conventional tariffs structure. Significant savings are observed when using a microgrid with DSM without causing a consumer change of habit.
Keywords: Demand-Side Management; Photovoltaic generation; White tariff; Distributed generation